Creatine kinase and neuromuscular indices of fatigue following elite rugby league match-play - McLellan, C.; Lovell, D.; Ferris, D.; Climstein, M. (Journal of Science and Medicine in Sport, 2011)
The purpose of the research: The aim of the present study was to identify neuromuscular and biochemical markers of fatigue following elite Rugby League match-play. Methodology: Seventeen elite male Rugby League players were monitored for a single match. Peak rate of force development (PRFD), peak power (PP) and peak force (PF) were measured during a countermovement jump (CMJ) on a force plate pre and post match-play. Blood samples were collected 24 hr pre-match, 30 min pre-match, 30 min post-match and then at 24 hr intervals for a period of 120 hr to determine plasma creatine kinase concentration ([CK]). Results: There were significant (p < 0.05) reductions in PRFD and PP up to 24 hr post-match with PF significantly (p < 0.05) reduced 30 min post-match. Plasma [CK] significantly (p < 0.05) increased 30 min post-match with a peak [CK] occurring 24 hr post-match. Plasma [CK] remained significantly (p < 0.05) elevated for at least 120 hr post-match in comparison to 24 hr pre-match levels. There were significant correlations between plasma [CK] and PRFD 30 min post-match (p < 0.05, r = -0.64) and 24 hr post-match (p < 0.05, r = -0.58) compared to 30 min pre-match values. Conclusions: Results demonstrate that neuromuscular function is compromised for up to 48 hr following elite Rugby League match-play. Plasma [CK] remained elevated despite 120 hr recovery indicating that damage to muscle tissue following Rugby League match-play may persist for at least 5 days post-match. These data indicate that while a return to pre-match neuromuscular function is evident on day 3 post-match, training load should however be monitored for at least 5 days post-match to achieve full recovery and optimise subsequent performance following skeletal muscle damage sustained during elite Rugby League match-play.